GAMBARAN PENGETAHUAN IBU TENTANG STUNTING PADA BALITA DI POSYANDU DESA SEGARAJAYA KABUPATEN BEKASI - Idham Topik Yoga (2020)
Stunting is a nutritional problem that occurs in infants characterized by shorter height compared to children his age. Knowledge held by parents, especially toddlers, mothers about insight about stunting can be a determinant of mothers' attitude in maintaining health so that stunting is prevented.This research was conducted to identify the description of mother's knowledge about stunting in toddler, to get mothers' characteristic descriptions including: age, education, and job also to get mothers' knowledge de.scription about stunting in toddler. This research applied descriptive research method, with the research populations were mothers who live in the Integrated Healthcare Center of Segerajaya Village Bekasi Regency area. The sampling method used is purposive sampling. The data collection methods used are questionnaire, interview, literature, institution, service or agency that supported the research. Data analysis used is univariate analysis. The analysis result is from 136 respondents, the majority of respondents aged 36 to 45 years, secondary education, unemployed (housewives) and have adequate knowledge about stunting. It can be concluded that from 136 respondents aged 36 to 45 years as many as 73 respondents (53,7%). Toddlers' mothers with secondary education as many as 87 respondents (64%), and unemployed toddlers' mothers as many as 91 respondents (66,9%) Enough knowledge about stunting of 57 respondents (41.9%).The mothers' knowledge become the main thing in the household management, It is expected to be further enhanced for parents, especially mothers in their knowledge of stunting in infants. Recommended cross-sectional research design for further research in order to be able to further identify